Local Wisdom Practices in Managing Fisheries Resources of the Klawing River - Salsabila, Sahda; Junaidi, Teuku; Suweda Anggana Putera, I Gede; Pramono, Taufik Budhi; Situmorang, Sawitania Christiany Dwi Utami Boru; Windiarta, Talitha Putri; Putri, Indah Karunia; Rizkiana, Fidia Indah; Saprudin, Saprudin; Winarno, Gunardi Djoko (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
The Klawing River plays an essential role as a source of livelihood for local communities and as a habitat for various fish species, yet it is increasingly under pressure from human activities and environmental changes. This study aims to identify the forms of local wisdom practiced by fishing communities in managing fishery resources and to assess their relevance to modern challenges. The research was conducted in five villages representing the upstream, middle, and downstream sections of the river using a qualitative descriptive approach through interviews and observations involving 40 respondents. The results show that local wisdom is reflected in the use of traditional fishing gear (nets, gillnets, fishing lines, paser, wuwu, and mijahan), the application of the pranata mangsa as a seasonal fishing guide, social solidarity among fishers, and the Gredug Sampah tradition focused on maintaining river cleanliness. These practices now face limitations due to climate change, the introduction of invasive species, and economic pressures. The declining accuracy of the pranata mangsa indicates the need to integrate traditional ecological knowledge with modern climatological information to enhance community adaptation to ecosystem dynamics. Therefore, the synergy between local wisdom and scientific approaches is crucial for achieving an adaptive and sustainable fishery resource management system in the Klawing River.